Energy Management System Using a Fuzzy Logic Controller for Grid-Connected Hybrid Renewable Energy Sources. - Fatima Menzri; Tarek Boutabba; Rachid CHENNI (university Of Eloued جامعة الوادي, 2020)
This paper presents a comparison study between a conventional energy management systems (EMS) based on a PI controller and an intelligent technique. A Fuzzy Logic Controller (FLC) was studied to solve the EMS energy management system of an isolated system. This hybrid system including the photovoltaic system (PV), wind turbine system, an energy storage system (ESS) and a dump load. All energy sources are connected to a DC bus via a DC-DC power converter. The proposed strategy for the energy management system in this design is to determine the power to be generated by the ESS using a conventional EMS and a new EMS (FLC), taking into account the power generated by the main resources (PV, wind), the power demanded by the grid and the state of charge (SOC).
Intervention
Keywords: PV; wind; Renewable sources; Power management; PI controller; fuzzy logic